The Care cooperatives and territorial development: Reflections on a project promoted in the City of Trelew, Chubut, Argentina - Freytes Frey, Marcela Ines; Veleda, Marina (Cooperativismo & Desarrollo, 2021)
This article proposes to reflect on and present a systematization of the progress of the project “Trelew Ciudad de Cuidados: towards a network of work cooperatives that promote sustainable local development”, promoted by the Universidad de Chubut, Argentina during 2019 and 2020. This action research project responds to the needs of the city associated with population, cultural and economic changes that increase the care needs of specific groups, such as the elderly or disabled and children. Through articulated work and co-responsibility between the University, the Municipal and Provincial State, and community organizations, it has been propo-sed to develop a collective and participatory response to promote local productive development, incorporating the gender perspective and promoting models of innovative management. Thus, it seeks to make visible and recognize the importance of care work, which is crossed by a history of unequal distribution of responsibilities with strong inequality towards women, which generates disparities in the community system. Based on local knowledge about the problem, the project has developed a training process and is accompanying and incuba-ting work cooperatives that provide care services, made up of groups in vulnerable situations. In this work, the main conceptual axes on which the project is based are retaken and problematized and some partial results of its execution are presented
Keywords: Care; cooperatives; public policies